Intussusception in the adult: clinical, radiological and histological features. - Courtney, S. P. (BMJ Group, 1992)
Intussusception in the adult is an unusual cause of bowel obstruction. Unlike in childhood the clinical presentation is not clear cut and there are no distinct pathognomonic features. The radiological features are variable. Five patients presented to Frenchay Hospital over a five month period. The patients' clinical courses demonstrate the differing presenting features. Ultrasound investigation and CT scanning may show characteristic signs. Surgical treatment is mandatory as there is nearly always an underlying pathological abnormality which may be malignant.